The Reform of Arabic Grammar in Ulul Albab by Ahmad Rifa’i: A Syawqi Dhoif-Inspired Contribution to Islamic Economic Literacy - Hibatin Wafiroh; Moh. Sholeh Afyuddin; Ahmad Rifa'i; Fahma Lailatul Fitriyah (International Conference on Islamic Economic (ICIE), 2025)
The study addresses the contemporary challenge of revitalizing Arabic grammar (nahwu) learning by examining the integration of classical and modern approaches within Islamic scholarship. This research has two primary objectives: first, to analyze how Arabic grammar material is presented in Ulul Albab by Ahmad Rifa’i; and second, to evaluate this presentation using Shawqi Dhoif’s theory of nahwu renewal. The research employs a qualitative design with a library research approach. Data collection was conducted through documentation and interviews: documentation involved the analysis of Ulul Albab and Shawqi Dhoif’s Tajdīd al-Nahw, while interviews were carried out with the author of Ulul Albab to strengthen the validity of interpretation. The findings reveal that Ulul Albab, completed in 2022 as Ahmad Rifa’i’s doctoral dissertation, systematically presents Arabic grammar rules accompanied by varied sentence examples, references to classical nadhm traditions, and practice exercises designed to enhance student comprehension. Analysis using Shawqi Dhoif’s renewal theory shows that four aspects of Rifa’i’s work align with the reformist perspective, while two aspects diverge or even contradict, largely due to the differing intellectual backgrounds: Ulul Albab draws heavily from classical grammatical works, whereas Tajdīd al-Nahw reflects Ibn Mada’s rationalist and textualist orientation. This research contributes to the field of Arabic linguistic studies and Islamic economics by demonstrating how nahwu renewal can promote more simplified, practical, and effective grammar instruction. Furthermore, it highlights the potential of Arabic literacy not only for academic learning but also for advancing Islamic economic literacy in contemporary contexts.